2023
DOI: 10.3390/cancers15010325
|View full text |Cite
|
Sign up to set email alerts
|

Role of Machine Learning (ML)-Based Classification Using Conventional 18F-FDG PET Parameters in Predicting Postsurgical Features of Endometrial Cancer Aggressiveness

Abstract: Purpose: to investigate the preoperative role of ML-based classification using conventional 18F-FDG PET parameters and clinical data in predicting features of EC aggressiveness. Methods: retrospective study, including 123 EC patients who underwent 18F-FDG PET (20092021) for preoperative staging. Maximum standardized uptake value (SUVmax), SUVmean, metabolic tumour volume (MTV), and total lesion glycolysis (TLG) were computed on the primary tumour. Age and BMI were collected. Histotype, myometrial invasion (MI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Therefore, as a tumor becomes increasingly undifferentiated and aggressive, it results in elevated glucose utilization and increased uptake of the radioactive tracer 18 F-FDG. 19 , 20 Black patients with breast cancer have poorer prognosis and higher mortality. Abubakar et al 19 observed differences in 18 F-FDG PET–CT metabolic parameters of locally advanced invasive ductal carcinoma (IDC) among patients of different racial groups and molecular subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as a tumor becomes increasingly undifferentiated and aggressive, it results in elevated glucose utilization and increased uptake of the radioactive tracer 18 F-FDG. 19 , 20 Black patients with breast cancer have poorer prognosis and higher mortality. Abubakar et al 19 observed differences in 18 F-FDG PET–CT metabolic parameters of locally advanced invasive ductal carcinoma (IDC) among patients of different racial groups and molecular subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET–CT parameters offer metabolic information that can be used to evaluate tumor aggressiveness, 18 - 20 predict lymph node metastasis (LNM) 21 - 23 and may be correlated with patient survival. 24 The maximum standard uptake value (SUV max ) is the most commonly used metabolic parameter.…”
Section: Introductionmentioning
confidence: 99%
“…This approach aims to be more closely aligned with clinical practice, providing guidance for patient surgery, adjuvant therapy, and prognosis assessment. Carolina Bezzi [ 36 ] investigated the role of machine learning (ML)-based classification using PET parameters in predicting features of EC aggressiveness, aiming at supporting the clinical decision-making process. Thus we would further our search involving the accuracy and predictive ability of PET/CT for the assessment of high-risk factors in EC patients according to 2023 new FIGO staging or use machine learning (ML) in the future.…”
Section: Discussionmentioning
confidence: 99%